Advanced Financial and Risk Feasibility Assessment of Indonesia’s Binary Geothermal Plant with Carbon Credit Integration - Xiaojun, Yan; Hakam, Dzikri Firmansyah (International Journal of Energy Economics and Policy, 2024)
Global warming is a pressing issue. NASA has predicted that 15 Southeast Asian islands will be submerged by 2100, as a result of a 0.77 cm increase in global sea levels from 2022 to 2023. Global temperatures were 1.48°C higher than pre-industrial levels in 2023. Indonesia must increase the use of renewable energy sources and energy efficiency. By 2030, energy consumption will rise by 3% and power demand by 8.5%, with fossil fuels meeting two-thirds of demand and CO2 emissions rising 35%. This study evaluates the techno-economic feasibility of a 60 MW Indonesian Organic Rankine Cycle (ORC) geothermal power plant using carbon credits. Indonesia’s geothermal potential is 40% of global resources, but high upfront costs, insufficient regulatory support, and technical obstacles limit development. Flexible and efficient ORC geothermal power generation provides steady baseload power for low to medium-temperature resources. This study applies RETScreen software for techno-economic analysis, sensitivity, and risk assessment to analyze project feasibility under multiple scenarios. Initial costs, operation and maintenance expenditures, energy generation, and GHG reductions are analyzed in detail. Net Present Value (NPV), Internal Rate of Return (IRR), and Levelized Cost of Energy (LCOE) were calculated for four scenarios: minimal incentives, increased carbon credit incentives, extended project lifespan with tax benefits, and optimized scenarios with high carbon credit prices. With a pre-tax equity IRR of 20.7% and an NPV of 97.52 million, the project is commercially viable at 2/ton CO2 in Indonesia. Raising the carbon credit price to 18/ton CO2 boosts IRR to 26.1% and NPV to 142.74 million. An equity payback period of 2.9 years and decreased LCOE is achieved by extending the project lifespan to 30 years and using a carbon credit price of 46/ton CO2. These data show how carbon price affects geothermal investment profitability. Optimizing geothermal exploration and adopting innovative technologies can cut expenses and speed up progress. Inspired by the Philippines and Kenya, government incentives, tax cuts, and faster approvals can make geothermal projects financially viable, helping Indonesia reach its 2060 zero carbon emissions objective.